2023
DOI: 10.3389/fphar.2023.1136317
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics analyses reveal ClpP activators disrupt essential mitochondrial pathways in triple-negative breast cancer

Abstract: ClpP activators ONC201 and related small molecules (TR compounds, Madera Therapeutics), have demonstrated significant anti-cancer potential in vitro and in vivo studies, including clinical trials for refractory solid tumors. Though progress has been made in identifying specific phenotypic outcomes following ClpP activation, the exact mechanism by which ClpP activation leads to broad anti-cancer activity has yet to be fully elucidated. In this study, we utilized a multi-omics approach to identify the ClpP-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Two of the most potent TR compounds, TR-57 and TR-107, were found to have significant effects on POLRMT [34,38], which will be discussed in more detail below. Though ClpP activation results in the widespread loss of mitochondrial matrix proteins [38], identification of specific ClpP substrates is still being pursued. Recent studies identified multiple ClpP-interacting proteins and putative substrates through proximity ligation (Bio-ID) and N-terminome (HYTANE) profiling methods [35,76].…”
Section: Small Molecule Clpp Agonists As Anti-cancer Compoundsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two of the most potent TR compounds, TR-57 and TR-107, were found to have significant effects on POLRMT [34,38], which will be discussed in more detail below. Though ClpP activation results in the widespread loss of mitochondrial matrix proteins [38], identification of specific ClpP substrates is still being pursued. Recent studies identified multiple ClpP-interacting proteins and putative substrates through proximity ligation (Bio-ID) and N-terminome (HYTANE) profiling methods [35,76].…”
Section: Small Molecule Clpp Agonists As Anti-cancer Compoundsmentioning
confidence: 99%
“…This difference in treatment response indicates that there are significant differences in the mechanism of action of these drug classes. Most notably, ClpP agonists are known to impact a number of metabolic pathways that are required for cancer cell proliferation (i.e., proline biosynthesis and heme biosynthesis pathways) [38,78]. Table 1 compares cell lines where IC 50 data for both IMT1 and ClpP agonists has been obtained.…”
Section: Differences In Treatment Response Timesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these interactions are indeed becoming interesting clues towards targeted therapy. Such is the case of the mechanisms by which the mitochondrial protease ClpP is activated by drugs that are able to breakdown essential mitochondrial pathways in triple-negative breast cancer ( 113 ). Similarly, the role of heat shock proteins (which may be either acting as oncogenes and onco-suppressor genes) has been recently discussed at the light of multi-omic analysis ( 114 ).…”
Section: Applications Of Concerted Multi-omic Regulation Analysis In ...mentioning
confidence: 99%